Bluetongue in India: a systematic review and meta-analysis with emphasis on diagnosis and seroprevalence - Rupner, Ramkumar N. (Vet Q, 2020)
Bluetongue (BT) is an infectious viral disease which affects a wide range of ruminants and was first reported in India in 1964. In view of the absence of comprehensive information on the BT status in India, this study presents the seroprevalence on BT in farm animals of India based-on a systematic review and meta-analysis. A systematic review was conducted to identify the published articles (2001–2018) reporting the seroprevalence of BT in sheep, goats, cattle, buffalo, camels, and Mithun (Bos frontalis) from India. From 409 research articles, 71 fulfilled the inclusion criteria and meta-analysis for proportions was carried out targeting the eligible studies. From these, 144 strata level data were extracted with a sample size of 14048 sheep, 14696 goats, 5218 cattle, 2653 buffaloes, 2062 camels, and 222 Mithun. Overall, the analyses showed that the BT seroprevalence of 43% (95% CI: 38–49%) in goats, 39% (95% CI: 33–46%) in sheep, 38% (95% CI: 25–45%) in cattle, 34% (95% CI: 20–51%) in buffaloes, 16% (95% CI: 10–22%) in camels, and 66% (95% CI: 17–95%) in Mithun. Furthermore, the meta-regression analysis suggested that serological tests, geographical region, and sample size were the prime moderators. Meta-analytic study indicates the BT seropositivity in 25.35 million sheep (95% CI: 21.5–29.9), 58 million goats (95% CI: 51.3–66.2), 66.8 million cattle (95% CI: 47.7–86), 37.0 million buffaloes (95% CI: 21.7–55.4), 0.06 million camels (95% CI: 0.04–0.09), and 0.19 million Mithun (95% CI: 0.05–0.28). The findings highlight the variation of BT seropositivity in different geographical regions of India.